PENGARUH KETERAMPILAN KONSEPTUAL KEPALA SEKOLAH TERHADAP KINERJA SEKOLAH - Zukfikar Zulfikar; Nuryani Nuryani; Alia Lestari (Institut Agama Islam Negeri (IAIN) Palopo, 2021)
This study aims: to see the ability of the principal's skills, to see school performance and to react to the effect of the principal's conceptual skills on school performance. The research method used is quantitative research with the type of research is ex post facto. The population is all teachers at SMP Negeri 4 Palopo. The sampling technique used was saturated sampling. The sample used was 40 teachers. Data obtained through questionnaires and documentation. Furthermore, the research data were analyzed using statistical data processing, namely: descriptive statistics and inferential statistics. The results of descriptive research show that the conceptual skills of the principal in SMP Negeri 4 Palopo have a score of 84.45 and a variance of 86.237 with a Standard Deviation of 9, 286 from the lowest score of 62 and the lowest score of 100 are in the very good category and school performance in SMP Negeri 4 Palopo has a mean score of 84.62 variants of 49,400 with a standard deviation of 7,028 from the lowest score of 72 and the highest score of 100 is included in the very good category. The results of research and data analysis carried out from the conceptual skills of school principals (X) have an effect on school performance (Y) which can be seen that the value of T count 8.888 is greater than T table whose value is 1.686 and the significant value of the principal's conceptual skills is 0.000 <0.05. R2 (R square) of 0.675 or equal to 57.5% means that H0 is rejected and H1 is accepted. So it can be interpreted that the conceptual skills of the principal have an effect on the performance of schools in SMP Negeri 4 Palopo.